CONSTITUTIONAL FOUNDATIONS OF PROPERTY RIGHTS IN A DEMOCRATIC STATE - Dzhafarov, Navai; Volochkova, Marina; Ivanova, Svetlana; Alekseev, Igor; Dzhandubaev, Zaur (Revista Inclusiones, 2020)
The relevance of the research lies in the fact that there is still no universal constitutional definition of property in the foreign scientific literature. The understanding and constitutional and legal regulation of property as a universal institution resulted from the development of both the economic basis of property relations and the legal system in European countries, including that resulted from the democratic constitutions adopted in these countries.